2007
DOI: 10.1177/0363546507305011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Acute versus Chronic Bony Bankart Lesions Managed Arthroscopically

Abstract: An arthroscopic procedure using suture anchors appears to enable successful treatment of acute bony Bankart lesions. Chronic lesions had less favorable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
103
3
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 45 publications
2
103
3
10
Order By: Relevance
“…The reliability of this new tool however needs to be confirmed by specific studies as it has not yet been validated. The results concerning return to sports are similar to those reported in the literature [17,24,25,27]. Concerning apprehension, we found that, regardless of the procedure performed; about 20% of shoulders had persistent anterior apprehension (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The reliability of this new tool however needs to be confirmed by specific studies as it has not yet been validated. The results concerning return to sports are similar to those reported in the literature [17,24,25,27]. Concerning apprehension, we found that, regardless of the procedure performed; about 20% of shoulders had persistent anterior apprehension (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Since then, several arthroscopic techniques using suture anchors have been reported to treat bony Bankart lesions. 12,16,29) However, there are some limitations to these techniques. For example, the suture anchor technique does not provide sufficient contact area for the fractured fragment because the suture crosses the surface of the fracture, and the bony fragment may tilt because of the one-point fixation.…”
Section: Discussionmentioning
confidence: 99%
“…An arthroscopic technique has many advantages, such as anatomic repair with a direct view, decreased invasiveness and tissue trauma, and a concomitant pathological diagnosis. Many arthroscopic methods have been used; 8,10,13,[15][16][17][18] however, they all have major limitations, including technical challenge.…”
mentioning
confidence: 99%
“…[2][3][4][5] The existence of numerous methods is evidence that there is still no established method for surgery.In the 2000s, new methods utilizing suture anchors were designed. However, this technique could not provide sufficient contact area for the fractured fragment because the suture crossed the surface of the fracture and the bony fragment could tilt because of the one-point fixation.…”
mentioning
confidence: 99%
“…[2][3][4][5] The existence of numerous methods is evidence that there is still no established method for surgery.…”
mentioning
confidence: 99%